Evaluasi Kinerja Pelayanan Administrasi Kependudukan di Desa Pinang Mas Kecamatan Sungai Pinang Kabupaten Ogan Ilir - Indra Gunawan; Alamsyah Alamsyah; Mega Nugraha (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Indra Gunawan. Village government is the lowest hierarchy in the bureaucratic system in Indonesia, therefore the role of village government is very important in providing services to village communities, this is the responsibility of the village government in providing maximum service. The purpose of providing services is to fulfill the basic needs and rights of every citizen and population for an administrative service provided by the government for the public interest, one type of public service is public service in the field of population administration. However, all service activities need to be evaluated to assess and ensure that population administration services are running in accordance with the regulations and expectations of the community. In this study the authors took the title